การสร้างแบบทดสอบทักษะกีฬาวอลเลย์บอล สำหรับนักเรียน ชั้นประถมศึกษาปีที่ 6 โรงเรียนศรีจิตรา จังหวัดปทุมธานี - จั่นจุ้ย, นภชา (Academic Journal Phranakhon Rajabhat University, 2017)
The purpose of this research was to study Construction of Volleyball Skills Rating Scale for Grade 6 Srijitra School in Pathum Thani Province, which were movement skills, under passing skills, setting skills and serving skills. There were 7 experts for checking rating scales to find Content Validity by Rovinelli and Hambleton methods, Reliability by Test–Retest, and Objectivity by using two estimators. A sample group was 6th Grade students from Srijitra School who were studying Volleyball during early year of 2013. A researcher separated the sample group into two groups which came from Sample Random Sampling by using drawing. Two sample groups were 30 male students and 30 female students, and overall was 60 students The result shows that volleyball skills rating scales has content validity of movement skills, under passing skills, setting skills and serving skills for 1.00, which can be measured along with a real behavioral objectives. Reliability and Objectivity have objectivity values on good to excellence levels which equals 0.97 within standard of volleyball skills. The 6th Grade students of Srijitra School, Pathumthani Province can be used for estimating volleyball skills.